BURNOUT AS A MEDIATOR OF TRAIN DRIVERS’ PERFORMANCE IN WORK SHIFTS STUDY AT PT KERETA API INDONESIA (PERSERO) - Priatna; Dwiputrianti, Septiana; Jubaedah, Edah; Pradesa, Hafid Aditya (Institut Riset dan Pengembangan Indonesia, 2026)
Safety and performance of train drivers are crucial factors in railway operations. Shift work systems involving night shifts, irregular rotations, and long working hours can lead to work-related fatigue (burnout), which impacts performance. This study aims to analyze the effect of work shifts on train driver performance with burnout as a mediating variable at PT Kereta Api Indonesia (Persero). The research uses a quantitative approach with a survey of 2,184 train drivers. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that work shifts have a significant positive effect on burnout (β = 0.608), work shifts have a significant negative effect on train driver performance (β = –0.339), and burnout has a very strong negative effect on performance (β = –0.839). Burnout significantly mediates the relationship between work shifts and performance, with a mediation effect of 51%. These findings emphasize that the decline in train driver performance is more influenced by burnout than by direct effects of work shifts. Comparatively, Japan’s fatigue management practices through a Fatigue Risk Management System (FRMS) are more systematic and preventive compared to Indonesia. This research contributes to strengthening the role of burnout as a mediating variable in the Job Demands–Resources framework and offers practical implications for PT KAI in reforming shift work policies for safety.